Fully Integrated Passive Wireless Sensor with Mechanical–Electrical Double-Gradient for Multifunctional Healthcare Monitoring - Zhou, Zhihao; Wu, Hongbing; Fu, Jingjing; Zhang, Gaoqiang; Li, Peng; Xia, Yushu; Wang, Xue; Li, Yuanyuan; Yang, Jin (Nano letters, 2024)
Accurate, effective, and continuous monitoring of pressure, moisture, and temperature is essential for routine health assessments and professional patient care. In this study, we present a fully integrated multiparameter passive wireless sensor (MWS) that employs a mechanical–electrical dual-gradient structure design. The unique gradient porous structure endows the MWS with significant advantages in terms of detection dimensions (pressure, moisture, and temperature), sensitivity, and stability. Compared to single mechanical gradient designs, the sensor demonstrates 2.6 times higher pressure sensitivity and a 5-tier moisture detection capability. By bridging the technology gap between high-precision multiparameter sensing, wireless communication, and energy management, the MWS is capable of measuring multiple physiological parameters, including breath, ballistocardiograph, moisture, and temperature at multiple points, providing real-time assessments of the physiological state of the subjects. This work offers valuable quantitative insights for caregivers and paves the way for significant advancements in personal healthcare management.